Творення системи військово-морської освіти в добу української революції 1917-1921 рр. - Лубенець, А.В. (Культура народов Причерноморья, 2013)
У статті висвітлюється організаційна діяльність українського Морського міністерства
щодо створення системи військово-морської освіти в добу Української революції 1917-1921 рр. Академія
ВМС імені П.С.Нахімова, ставши офіційним спадкоємцем Української гардемаринської школи -
навчального закладу, призначенням якого була підготовка морських офіцерів з числа українських
громадян для українського флоту - відчутно “подорослішає”. Її історія збагатиться яскравим
періодом державотворчої боротьби за створення системи військово-морської освіти в добу Української
революції 1917-1921 років. В статье освещается организационная деятельность украинского Морского
министерства по созданию системы военно-морского образования в сутки Украинской революции 1917-
1921 гг. Академия ВМС имени П.С. Нахимова, став официальным наследником Украинского
гардемаринськои школы - учебного заведения, назначением которого была подготовка морских
офицеров из числа украинских граждан для украинского флота - ощутимо "повзрослеет". Ее история
обогатится ярким периодом государственно борьбы за создание системы военно-морского образования
в сутки Украинской революции 1917-1921 годов. In article osveschaetsya Organizational Deyatelnost Sea Ukrainian Ministry for creation systems ,
military SEA education in day Ukrainskaia Revolution 1917-1921 biennium. Command of the formed Hetman of
Ukrainian Navy , strongly promoted the involvement of officers in the service of the "old" fleet. However, it
quickly became clear that this path is not promising. It is soon taken vigorous measures to establish a system of
training a new generation of officers - Ukrainian naval officers. This happened through appropriate education,
sound system of national military education. "For the Hetmanate management system training military
specialists conducted military Ofitsiya Ukrainian State and subordinate Home school council. They developed a
system of military education, asserted conditions for admission to the cadet corps and petty schools were
determined list of specialties , states, military schools and their funding, " - said M.I.NeschadymAkademyya
Navy behalf of PS Nakhimov became ofytsyalnыm Heir Ukrainian hardemarynskoy schools - uchebnoho
establishments of , appointment to kotorogo been Preparations for SEA officers ukrainskikh number of citizens
for the Ukrainian Navy - oschutymo " povzrosleet ." Her History obohatytsya striking period in struggle for the
creation of the State system of military- SEA education in day Ukrainskaia Revolution 1917-1921 hodov.At night
Hetmanat navy organization was part of the War Ministry, but the problem of training officers for the Navy, it
was to decide autonomously by creating their own schools. “Activities of the military departments to establish a
system of training of military specialists in this period shows that this issue consistently paid great attention.
Considering it as a priority of the state in creating their own armed forces”.